The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12885-020-07655-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term mortality risks among patients with non-metastatic bladder cancer

Abstract: Background Population-based analysis for the short-term non-bladder cancer related mortality among patients with non-metastatic bladder cancer is currently lacking. The objective of the current study was to assess and quantify cause of death after bladder cancer diagnosis. Methods The custom Surveillance, Epidemiology, and End Results (SEER) dataset for standardized mortality ratios (SMRs) was utilized to identify 24,074 patients who were diagnosed with nonmetastatic (M0) bladder cancer from 2014 to 2015. SMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…Secondly, overall survival could be influenced by non-cancer related co-morbid conditions. 14 Our study findings on higher mortality among older patients, and those with grade IV and multiple in-situ tumors align with the current evidence. 15,16 Literature shows that older patients are less likely to receive intravesical therapy.…”
Section: Discussionsupporting
confidence: 90%
“…Secondly, overall survival could be influenced by non-cancer related co-morbid conditions. 14 Our study findings on higher mortality among older patients, and those with grade IV and multiple in-situ tumors align with the current evidence. 15,16 Literature shows that older patients are less likely to receive intravesical therapy.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the procedure resulted in a limited postoperative complication rate. The mid-term oncological outcomes were in line with the survival estimates for urothelial bladder cancer [21,22]. As such, these findings support the findings from previous reports [6][7][8][9][10][11] regarding surgical safety while adding information in terms of midterm oncological outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…Recent European Association of Urology Guidelines lack recommendations on the risk of CVD-related death in older patients with BC and focus only on cancer-related deaths [ 9 , 10 ]. Although current studies have reported higher proportions of noncancer deaths (including CVD-related deaths) among all BC patients [ 11 , 12 , 13 , 14 , 15 , 16 ] and nonmetastatic BC patients [ 17 ], such studies have not compared the transforming trend of the competing risks of CVD and BC-related death. Furthermore, because these studies lack stratification according to different age subgroups, their results may not be generalizable to older BC patients [ 11 , 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although current studies have reported higher proportions of noncancer deaths (including CVD-related deaths) among all BC patients [ 11 , 12 , 13 , 14 , 15 , 16 ] and nonmetastatic BC patients [ 17 ], such studies have not compared the transforming trend of the competing risks of CVD and BC-related death. Furthermore, because these studies lack stratification according to different age subgroups, their results may not be generalizable to older BC patients [ 11 , 12 , 17 ]. Most studies have simply delineated the composite CVD death outcome or specific CVD death outcomes, such as fatal heart disease [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%